Institutional Trust as A Governance Mechanism in Dual Governance Systems of Indonesian Private Universities - Graverra Personata; Eko Handoyo; Widiyanto Widiyanto (Proceedings of International Conference on Science, Education, and Technology, 2026)
Governance effectiveness in Indonesian private universities is often challenged by dual governance arrangements involving foundations and university leadership. While previous studies have primarily explained these relationships through Agency Theory, emphasizing monitoring, control, and accountability mechanisms, limited attention has been given to the role of institutional trust in facilitating effective governance. This study aims to explore how institutional trust functions as a governance mechanism within dual governance relationships in Indonesian private universities. A qualitative multiple-case study design was employed involving four private universities in Indonesia: Universitas Muhammadiyah Purwokerto (UMP), Universitas Muhammadiyah Semarang (UNIMUS), Universitas Islam Sultan Agung (UNISSULA), and Universitas Pancasakti Tegal (UPS). Data were collected through semi-structured interviews with foundation representatives, governing board members, rectors, and senior university leaders and analyzed using thematic analysis. The findings revealed four interrelated dimensions through which institutional trust operates. First, transparency and accountability strengthened confidence through open reporting and information sharing. Second, role clarity and clearly defined authority boundaries reduced uncertainty and supported cooperative governance relationships. Third, formal and informal communication facilitated mutual understanding and conflict prevention. Fourth, shared institutional values, including Al-Islam dan Kemuhammadiyahan (AIK), amanah wakaf, and professionalism, reinforced collective commitment to institutional goals. Across all cases, trust emerged as a complementary governance mechanism that supported collaboration between principals and agents alongside formal governance structures. The study concludes that governance effectiveness in private universities cannot be fully explained through traditional Agency Theory alone. A Trust-Based Governance Perspective is proposed, highlighting institutional trust as a critical mechanism that enhances governance effectiveness and institutional sustainability within dual governance environments.